New seminal plasma removal method for freezing stallion semen - Ramires Neto, C. [UNESP]; Monteiro, G. A. [UNESP]; Soares, R. F. [UNESP]; Pedrazzi, C.; Dell'aqua Junior, José Antônio [UNESP]; Papa, Frederico Ozanam [UNESP]; Castro-Chaves, M. M. [UNESP]; Alvarenga, Marco Antonio [UNESP] (Elsevier, 2013)
Seminal plasma removal, an indispensable step in equine semen cryopreservation, is usually done by centrifugation, but this might cause mechanical damage to sperm. A new method for seminal plasma removal from stallion semen, namely a filter composed of a synthetic hydrophilic membrane (Sperm Filter, BotuPharma, Botucatu, Sao Paulo, Brazil), was recently proposed. The objective of this study was to test the use of the Sperm Filter in the removal of seminal plasma before freezing stallion semen. Ejaculates from 31 stallions were divided into two groups and cryopreserved. In group 1 (G1), seminal plasma was removed with the Sperm Filter, and in group 2 (G2), seminal plasma was removed by centrifugation (600× g for 10 minutes). There were no differences (P < 0.05) between G1 and G2 in sperm kinetic parameters or plasma membrane integrity before or after cryopreservation. However, sperm recovery rate was higher (P < 0.05) for G1 versus G2 (mean ± SD, 89.4 ± 7.4% vs. 80.9 ± 5.5%). Therefore, the Sperm Filter was as efficient as centrifugation in removing seminal plasma from the stallion ejaculate. However, filtering was more practical and had significantly fewer sperm lost than the centrifugation technique. © 2013 Elsevier Inc.
Keywords: Centrifugation; Horse; Semen; Seminal plasma; Sperm filter; Stallion